Model Analyses of Changes in Spring Surface Ozone Concentrations over Shandong Province in the Period of 2014–2017 - Jialin Li; Juzhen Cai; Houfeng Liu; Xiao Han; Yongfu Xu; Xiaofang Cai; Meigen Zhang (Aerosol and Air Quality Research)
Abstract The concentrations of surface ozone (O3) in eastern China have increased significantly in recent years, resulting in the earlier appearance of more serious O3 pollution. Measurements at 14 stations in Shandong Province showed that the monthly mean O3 concentrations in the late spring (May) increased by 22.2 µg m−3 from 2014 to 2017. To investigate the reasons of the increase of O3 in springtime from 2014 to 2017, the changes of O3 concentrations due to meteorological conditions and emissions in May were studied based on ambient measurements and simulations with the RAMS-CMAQ modeling system. By analyzing the observed data, it was found that the variations in wind field were conducive to the accumulation of O3, while the effects of other meteorological parameters on O3 concentrations were different at the same site between years. Further to perform a series of simulations with only the meteorological conditions changed in May from 2014 to 2017, the results showed that the effects of variations in meteorological conditions had become more and more important in the changes of O3 concentrations in May between years, especially the factors that affected the photochemical generation of O3. For example, the percentage of the sites where the changes of O3 concentrations were dominated by the variations of the meteorological conditions increased from 28.6% to 78.6% over the region in May between years. Besides, the changes in NOx emissions had a close relationship with the variations in O3 concentrations when the changes of O3 were dominated by the emission variations.